EDUCATIONAL AWARENESS OF THE HISTORICAL HERITAGE OF SERRA DA CAXEXA: ADVANCES AND SETBACKS - Regina Ribeiro de Araújo Medeiros, Leize (Revista Gênero e Interdisciplinaridade, 2023)
The following article aims to direct the studies of archaeological sites in the Agreste region of Paraíba, more specifically in Serra da Caxexa, in the municipality of Casserengue – PB, 154 km from the capital, João Pessoa, developing the cataloguing, mapping and description of prehistoric sites existing there in order to contribute to their preservation process. Archaeological research in the State of Paraíba finds evidence of more than 500 archaeological sites, among these are the rock art sites “Pedra do Caboclo” and “Pedra do Letreiro”, belonging to the cultural universe of the Agreste Tradition, indicating strong evidence from the passage of indigenous groups that populated the Eastern Curimataú region before the European colonization process, being probably represented by the Sucurus of the Tarairiú nation with semi-nomadic characteristics. Cave paintings are classified as anthropomorphic, zoomorphic and geometric/schematic, generally in reddish tones resulting from the use of iron oxide. Unfortunately, the lack of knowledge about these archaeological sites leads to their destruction. Therefore, it is necessary to make all segments of society aware of the importance of the region’s archaeological heritage, seeking to await them for the knowledge of future generations and encourage new research that would rescue the historical value of local and regional culture. Thus, as an awareness of society in general, as a way of clarifying the importance of the historical and cultural heritage that surrounds them.